A collaborative key management scheme for distributed smart objects. Issue 6 (28th May 2017) - Hendaoui, Fatma; Eltaief, Hamdi; Youssef, Habib
Abstract: Secure communication of Internet of Things (IoT) devices relies on cryptographic approaches whose robustness is based on the security of encryption keys. For instance, an adequate key management scheme must be used to properly manage the used keys. Designing an efficient and robust key management scheme for the connected devices is a challenging task. Reported key management schemes suffer from several deficiencies such as the single point of failure and the non–trade‐off between scalability, connectivity, and resiliency. This paper first reviews key management schemes in the context of the IoT. Then, we propose a collaborative lightweight key management scheme that secures the keys during the life cycle of the embedded devices. Our proposal relies on the collaboration of the smart devices, where all the devices participate in the construction of the global key. Following the analytical and the comparative studies, we show that our proposal can be integrated in several communication protocols designated for embedded devices such as IEEE 802.15.4. Simulation results validate the analytical study and show that the proposed collaborative group key scheme exhibits superior performance when compared with two corresponding schemes reported in the literature. Abstract : This paper proposes a collaborative key management scheme for smart devices. The proposed solution respects the restraints of IoT devices such as processing, storage and communication resources. The key update does not engender further costs.